2022
DOI: 10.3390/molecules27134204
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Phytochemicals Derived from Roots of Rondeletia odorata as Antioxidant, Antiulcer, Diuretic, Skin Brightening and Hemolytic Agents—A Comprehensive Biochemical and In Silico Study

Abstract: Roots of Rondeletia odorata are a rich source of phytochemicals with high antioxidant potential and thus may possess health benefits. This study used the LC-MS technique to identify phytoconstituents in R. odorata roots extract/fractions. Results revealed that n-butanol fraction and ethanolic extract contained total phenolic and flavonoid contents with values of 155.64 ± 0.66 mgGAE/g DE and 194.94 ± 0.98 mgQE/g DE, respectively. Significant potential of antioxidants was observed by DPPH, CUPRAC and FRAP method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…The maximum hemolytic value was 14.5 ± 1.20% for NBVO and the minimum hemolytic value was 6.5 ± 0.94% for CRVO. Results confirmed that V. officinalis is a safe and non-toxic plant due to less than 30% of hemolysis activity [ 1 ].…”
Section: Resultsmentioning
confidence: 65%
See 3 more Smart Citations
“…The maximum hemolytic value was 14.5 ± 1.20% for NBVO and the minimum hemolytic value was 6.5 ± 0.94% for CRVO. Results confirmed that V. officinalis is a safe and non-toxic plant due to less than 30% of hemolysis activity [ 1 ].…”
Section: Resultsmentioning
confidence: 65%
“…The IC 50 value for Urease inhibition of Terminalia neotaliala different extract/fractions is 1.79−3.54 mg·mL −1 [ 62 ]. The different extract/fractions of Rondeletia odorata at a concentration of 5 mg·mL −1 revealed urease inhibition of 45.69–73.39% [ 1 ]. The significant urease inhibitory activity of EAVO may be validated due to some bioactive constituents found in GC-MS of ethyl acetate fraction such as 9,12-Octadecadienoic acid (Z,Z)-, methyl ester [ 63 ], 2-Cyclopenten-1-one, 3-methyl- [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is important to evaluate the possible hemolytic activity of a number of the frequently used herbs. When there is more than 30% hemolysis, the plant extracts are thought to be harmful to erythrocytes [ 73 ]. Table 7 displays the hemolytic activity of aerial parts of the entire F. vasta plant.…”
Section: Discussionmentioning
confidence: 99%